23.4% Saline Decreases Brain Tissue Volume in Severe Hepatic Encephalopathy as Assessed by a Quantitative CT Marker. Issue 1 (January 2016) - Liotta, Eric M.; Lizza, Bryan D.; Romanova, Anna L.; Guth, James C.; Berman, Michael D.; Carroll, Timothy J.; Francis, Brandon; Ganger, Daniel; Ladner, Daniela P.; Maas, Matthew B.; Naidech, Andrew M.
Abstract : Objective: Cerebral edema is common in severe hepatic encephalopathy and may be life threatening. Bolus 23.4% hypertonic saline improves surveillance neuromonitoring scores, although its mechanism of action is not clearly established. We investigated the hypothesis that bolus hypertonic saline decreases cerebral edema in severe hepatic encephalopathy utilizing a quantitative technique to measure brain and cerebrospinal fluid volume changes. Design: Retrospective analysis of serial CT scans, and clinical data for a case-control series were performed. Setting: ICUs of a tertiary care hospital. Patients: Patients with severe hepatic encephalopathy treated with 23.4% hypertonic saline and control patients who did not receive 23.4% hypertonic saline. Interventions: 23.4% hypertonic saline bolus administration. Measurements and Main Results: We used clinically obtained CT scans to measure volumes of the ventricles, intracranial cerebrospinal fluid, and brain using a previously validated semiautomated technique (Analyze Direct, Overland Park, KS). Volumes before and after 23.4% hypertonic saline were compared with Wilcoxon signed rank test. Associations among total cerebrospinal fluid volume, ventricular volume, serum sodium, and Glasgow Coma Scale scores were assessed using Spearman rank correlation test. Eleven patients with 18 administrations of 23.4% hypertonic saline met inclusion criteria. Total cerebrospinal fluid (median, 47.6 mL [35.1–69.4 mL] to 61.9 mL [47.7–87.0 mL]; p < 0.001) and ventricular volumes (median, 8.0 mL [6.9–9.5 mL] to 9.2 mL [7.8–11.9 mL]; p = 0.002) increased and Glasgow Coma Scale scores improved (median, 4 [3–6] to 7 [6–9]; p = 0.008) after 23.4% hypertonic saline. In contrast, total cerebrospinal fluid and ventricular volumes decreased in untreated control patients. Serum sodium increase was associated with increase in total cerebrospinal fluid volume ( r = 0.83, p < 0.001), and change in total cerebrospinal fluid volume was associated with ventricular volume change ( r = 0.86; p < 0.001). Conclusions: Total cerebrospinal fluid and ventricular volumes increased after 23.4% hypertonic saline, consistent with a reduction in brain tissue volume. Total cerebrospinal fluid and ventricular volume change may be useful quantitative measures to assess cerebral edema in severe hepatic encephalopathy. Abstract : Supplemental Digital Content is available in the text.